PENINGKATAN HASIL BELAJAR SENAM LANTAI KAYANG MELALUI PEMBELAJARAN INTERAKTIF PADA SISWA KELAS XI TKI SMK YAYASAN PHARMASI - Wahyu Arbanisa; Affan Asy’ary; Sanjulyo Dhivalra Mashudhi; Muh Isna Nurdin Wibisana; Suwarso Suwarso (Journal of Physical Activity and Sports (JPAS), 2026)
The persistently low levels of student activity, self-confidence, and learning outcomes in the floor exercise backbend have become a challenge in Physical Education and Health (PJOK) lessons for Year XI TKI students at SMK Yayasan Pharmasi. Most students were still reluctant to perform the backbend, lacked self-confidence, and had not yet mastered the correct movement technique. This study aimed to improve students’ activity, self-confidence, and learning outcomes through interactive learning. The study employed Kurt Lewin’s Classroom Action Research (CAR) model, comprising the stages of planning, action, observation, and reflection. The research was conducted over two cycles involving 28 students. Data were collected through observation, performance assessment, documentation, and field notes. The results showed that student activity increased from 68% in Cycle I to 94% in Cycle II, whilst self-confidence increased from 58% to 90%. Students’ mean scores also improved from 81.50 to 93.18, and learning mastery increased from 71.43% to 100%. These improvements occurred after learning was conducted using videos, Zep Quiz, peer tutors, small-group exercises, and ball-based assistance. The research findings indicate that interactive learning plays a significant role in enhancing students’ engagement, self-confidence and ability to perform the backbend movement. Interactive learning can serve as an effective alternative for improving learning outcomes in Physical Education, particularly in the area of floor gymnastics involving the backbend movement.